Needs must: living donor liver transplantation from an HIV-positive mother to her HIV-negative child in Johannesburg, South Africa. Issue 5 (13th May 2019) - Etheredge, Harriet Rosanne; Fabian, June; Duncan, Mary; Conradie, Francesca; Tiemessen, Caroline; Botha, Jean
Abstract : The world's first living donor liver transplant from an HIV-positive mother to her HIV-negative child, performed by our team in Johannesburg, South Africa (SA) in 2017, was necessitated by disease profile and health system challenges. In our country, we have a major shortage of donor organs, which compels us to consider innovative solutions to save lives. Simultaneously, the transition of the HIV pandemic, from a death sentence to a chronic illness with excellent survival on treatment required us to rethink our policies regarding HIV infection and living donor liver transplantation . Although HIV infection in the donor is internationally considered an absolute contraindication for transplant to an HIV-negative recipient, there have been a very small number of unintentional transplants from HIV-positive deceased donors to HIV-negative recipients. These transplant recipients do well on antiretroviral medication and their graft survival is not compromised. We have had a number of HIV-positive parents in our setting express a desire to be living liver donors for their critically ill children. Declining these parents as living donors has become increasingly unjustifiable given the very small deceased donor pool in SA; and because many of these parents are virally suppressed and would otherwise fulfil our eligibility criteria as living donors. This paper discusses the evolution of HIV and transplantation in SA, highlights some of the primary ethical considerations for us when embarking on this case and considers the new ethical issues that have arisen since we undertook this transplant.